Bubble nucleation and dissolution in multicomponent fluids near a phase boundary using a rapid heat pulse. (July 2017) - Demur, Romain; Oukmal, Jed; Luu, Guillaume; Mousset, Cécile; Leman, Marie; Villares, Gustavo; Kerdraon, Margaux; Sullivan, Matthew; Harrison, Christopher
Highlights: Thermal pulse of pulsed wire immersed in fluid mixture characterized thermally. Thermal pulse used to measure phase envelope quickly by rapid nucleation of second phase. Bubble dissolution kinetics measured in single and multi-component fluids. Nucleation not observed above critical line. Morphologies of nucleated bubbles characterized in single and multi-component fluids. Abstract: We report a novel means of nucleating a second phase using a miniature thermal nucleation source that operates with fluid mixtures at elevated temperature and pressure. This rapid nucleation source locally creates a short-lived (millisecond) but large (up to 10 7 K/m) thermal gradient that we exploit to overcome the nucleation barrier in single and multicomponent fluids, eliminating the need for traditional mechanical agitation. We find good agreement between the phase envelope measured with this method and that measured using a conventional apparatus with mechanical agitation acting as a nucleation source for several binary alkane mixtures. Consistent with expectations, we find that thermal nucleation cannot trigger production of a second phase for temperatures and pressures higher than that of the critical point for single-component fluids, However, we find a range of temperatures and pressures completely outside the phase envelope for multi-component mixtures where thermal nucleation temporarily and anomalously appears to produce a second phase, contrary to expectations based on equilibrium thermodynamics. The relationship between the magnitude of undersaturation and the rate of bubble dissolution is studied in single and multi-component fluids. Direct observations of the morphology that is created during nucleation reveal a sharp interface between coalescing droplets, consistent with the second phase possessing an interfacial tension with respect to the continuous phase.